On The Ambiguous Sign of the Optimal Utilitarian Marginal Income Tax - Emanuel Hansen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The paper studies optimal income taxation in a model with labor supply responses at the intensive and the extensive margin. It is shown that a utilitarian desire for redistribution does not pin down the sign of the optimal marginal tax rate: labor supply may be downward distorted, undistorted, or even upward distorted at both margins. The paper provides suffi cient conditions for the optimality of an EITC-style tax/transfer scheme under which labor supply is upward distorted at both margins for some skill groups. Furthermore, the paper shows optimal upward distortions at the intensive margin are driven by a non-standard tradeoff between effi ciency at the intensive margin and effi ciency at the extensive margin.
Keywords: H21; H23; D82; 330